Immune checkpoint blockade reveals the stimulatory capacity of tumor-associated CD103+ dendritic cells in late-stage ovarian cancer. (2nd August 2016) - Flies, Dallas B.; Higuchi, Tomoe; Harris, Jaryse C.; Jha, Vibha; Gimotty, Phyllis A.; Adams, Sarah F.
ABSTRACT: Although immune infiltrates in ovarian cancer are associated with improved survival, the ovarian tumor environment has been characterized as immunosuppressive, due in part to functional shifts among dendritic cells with disease progression. We hypothesized that flux in dendritic cell subpopulations with cancer progression were responsible for observed differences in antitumor immune responses in early and late-stage disease. Here we identify three dendritic cell subsets with disparate functions in the ovarian tumor environment. CD11c+CD11b(−)CD103 + dendritic cells are absent in the peritoneal cavity of healthy mice but comprise up to 40% of dendritic cells in tumor-bearing mice and retain T cell stimulatory capacity in advanced disease. Among CD11c+CD11b+ cells, Lair-1 expression distinguishes stimulatory and immunoregulatory DC subsets, which are also enriched in the tumor environment. Notably, PD-L1 is expressed by Lair-1(hi) immunoregulatory dendritic cells, and may contribute to local tumor antigen-specific T cell dysfunction. Using an adoptive transfer model, we find that PD-1 blockade enables tumor-associated CD103 + dendritic cells to promote disease clearance. These data demonstrate that antitumor immune capacity is maintained among local dendritic cell subpopulations in the tumor environment with cancer progression. Similar dendritic cell subsets are present in malignant ascites from women with ovarian cancer, supporting the translational relevance of these results.